Intestinal Perforation by a Toothpick as Reason for Necrotizing Fasciitis - Rupp, Markus; Knapp, Gero; Weisweiler, David; Heiss, Christian; Alt, Volker; Justus Liebig University Giessen (My University, 2018)
Necrotizing fasciitis is an uncommon but often fatal disease. Given the various causes of necrotizing fasciitis, we report a case of sigmoid colon perforation caused by a toothpick subsequently resulting in fulminant necrotizing fasciitis of the retroperitoneum and right thigh successfully treated by hemipelvectomy and Hartmann´s procedure.
Keywords: intestinal perforation; necrotizing fasciitis; sepsis; hemipelvectomy; ddc:610